Between consent and conjugality: Deconstructing the legal and social barriers to the criminalization of Marital Rape in Contemporary India - Narayan, Pooja; Dixit, Harbansh (The International tax journal, 2026)
Marital rape the act of non-consensual sexual intercourse between spouses remains one of the most conspicuous legal blind spots in contemporary Indian jurisprudence. Despite constitutional guarantees of equality, dignity, and personal liberty under Articles 14, 15, and 21, India continues to extend criminal immunity to husbands who sexually coerce their wives, a position entrenched through Exception 2 of Section 375 of the Indian Penal Code, 1860, and its legislative successor, Exception 2 to Section 63 of the Bharatiya Nyaya Sanhita, 2023. This paper undertakes a comprehensive examination of the legal, constitutional, social, and institutional barriers that have persistently obstructed the criminalization of marital rape in India. Drawing upon constitutional jurisprudence, judicial decisions, legislative history, comparative international law, and sociological analysis, the paper argues that the marital rape exception (MRE) is constitutionally indefensible, socially regressive, and incompatible with India's obligations under international human rights law. The paper further contends that the continued existence of the MRE represents not merely a legislative oversight but a deliberate institutional choice rooted in patriarchal constructions of marriage, conjugal rights, and female sexuality.